A Limited Sampling Strategy for Therapeutic Drug Monitoring of Mycophenolate Mofetil for Prophylaxis of Acute Graft-Versus-Host Disease in Allogeneic Stem Cell Transplantation - Vikram Gota; Vaitashi Purohit; Murari Gurjar; Lingaraj Nayak; Sachin Punatar; Anant Gokarn; Avinash Bonda; Bhausaheb Bagal; Chakor Sunil Vora; Anand Patil; Manjunath Nookala; Navin Khattry (Cell Transplantation, 2020)
A universally accepted strategy for therapeutic drug monitoring (TDM) of mycophenolate mofetil (MMF) in the prevention of acute graft-versus-host disease (aGVHD) in allogenic hematopoietic stem cell transplantation (alloHSCT) does not exist. We explored the feasibility of developing a limited sampling strategy (LSS) for TDM of MMF in this setting. Patients undergoing alloHSCT received standard MMF-cyclosporine prophylaxis, with MMF administered twice daily (BD) for matched transplant recipients or thrice daily (TID) in haploidentical transplantation. Intensive blood sampling was carried out on day 7 and area under the concentration–time curve (AUC) of mycophenolic acid (MPA), the active metabolite, was estimated using noncompartmental analysis. The ability of MPA exposure defined by AUC 0-12 to discriminate between responders (patients who did not develop GVHD) and nonresponders (patients who developed GVHD) was determined by receiver operating characteristic curve analysis. Patients were divided into training and validation sets within BD and TID groups. Mathematical equations were developed from the training set to predict AUC 0-12 from an abbreviated AUC involving a limited number of sampling points. The equations were validated in the validation set by comparing the MPA AUC 0-12 predicted from LSS with the observed AUC 0-12 . It was observed that patients with AUC 0-12 ≤18.99 mg*h/L had a higher risk of developing aGVHD [odds ratio (OR) = 2.63 (1.17 to 5.87), P = 0.06]. The benefit was more in matched transplant recipients [OR = 3.5 (1.30 to 9.49), P = 0.05] as compared to haploindentical transplant [OR = 2.8 (0.49 to 15.91), P = NS]. Using the mathematical equations, the observed AUC 0-12 was predicted with 92.31% accuracy in the BD subset and 100% accuracy in the TID subset for a combined accuracy of 94.76%. A set of just three samples that constituted the abbreviated AUC 1-4 was used to develop the predictive models. The LSS could be employed for the therapeutic monitoring of MMF particularly in patients undergoing matched hematopoietic stem cell transplantation.